COMPUTATIONAL INTELLIGENCE IN SUSTAINABLE COMPUTING AND OPTIMIZATION trends and applications - Balusamy, Balamurugan; Ravi, Vinayakumar; Dhanaraj, Rajesh Kumar; Senthilkumar, S. 1973-; K., Brindha (MORGAN KAUFMANN PUBLISHER, 2024)
Computational Intelligence in Sustainable Computing and Optimization: Trends and Applications focuses on developing and evolving advanced computational intelligence algorithms for the analysis of data involved in applications, such as agriculture, biomedical systems, bioinformatics, business intelligence, economics, disaster management, e-learning, education management, financial management, and environmental policies. The book presents research in sustainable computing and optimization, combining methods from engineering, mathematics, artificial intelligence, and computer science to optimize environmental resources Computational intelligence in the field of sustainable computing combines computer science and engineering in applications ranging from Internet of Things (IoT), information security systems, smart storage, cloud computing, intelligent transport management, cognitive and bio-inspired computing, and management science. In addition, data intelligence techniques play a critical role in sustainable computing. Recent advances in data management, data modeling, data analysis, and artificial intelligence are finding applications in energy networks and thus making our environment more sustainable. Presents computational, intelligence-based data analysis for sustainable computing applications such as pattern recognition, biomedical imaging, sustainable cities, sustainable transport, sustainable agriculture, and sustainable financial management Develops research in sustainable computing and optimization, combining methods from engineering, mathematics, and computer science to optimize environmental resources Includes three foundational chapters dedicated to providing an overview of computational intelligence and optimization techniques and their applications for sustainable computing.
Keywords: Sustainable development -- Technological innovations; Artificial intelligence -- Environmental aspects; Computational intelligence; Développement durable; Innovations; Intelligence artificielle; Aspect de l'environnement; Intelligence informatique